Pregled očesnega ozadja bolnikov z arterijsko hipertenzijo v okviru minimalnega diagnostičnega programa - Petek Šter, Marija (Zdravstveno varstvo, 2003)
The eye fundus is a target organ of arterial hypertension, besides the heart, the kidneys and the vessels. Our aim was to check the feasibility of the eye fundus examination in a general practitioner's surgery. This cross-sectional study involved 50 non-diabetic patients with essential arterial hypertension, aged 40 to 69 years, who had no opacities of optic media and did not use eye-drops to lower high intraocular pressure. All subjects underwent the so-called "minimal" diagnostic programme ,including examination of the eye fundus with the direct ophthalmoscope, and were assessed for cardiovascular risk. In the year preceding the study, a complete minimal diagnostic programmewas carried out in only 11 (22%) hypertensive patients; the bottleneck was the eye fundus examination, perfomed by an ophtalmologist. The cardiovascular risk assessed by a method which takes into consideration the target organ damage was significantly increased (p<0.00001, c2). Examination of the eye fundus with the direct ophtalmoscope is feasible in a general practitioner's office. Damage to the target organ must be taken into consideration when assessing the cardiovascular risk in hypertensive patients.
Keywords: arterial hypertension; arterijska hipertenzija; cardiovascular risk; diagnostic programmes; diagnostični programi; eye fundus; kardiovaskularno tveganje; očesno ozadje